THE MANUFACTURE OF THE PROTOTYPE FIXED CRANE HARBOR AS THE ADDER DEVICE INSIGHT FOR CRANE OPERATOR NOVICE - Prautomo, Angga Agus; Atmiasri, Atmiasri (BEST, 2019)
Fixed cranes are tools used in the process of loading and unloading containers/materials from trucks and vice versa. Most of the young crane (beginners) operators in the port area are still unfamiliar in carrying out these tools, therefore the authors conduct research to make the fixedprototype crane that has functions and controls (including joystick) that allows the original device to remain valid. Insight enhancers in using real fixed cranes. The circuit built from Arduino Uno, DC motor (Gear Hoist and Gear Slewing), servo motor, and joystick as input for motion controllers from all systems. Fixed crane prototypes that have been made above are the best of the hoist system or the best slewing system todetermine the load that can be carried by the system. From the results of these calculations that the prototype fixed crane made has a maximum carrying capacity in terms of hoist and slewing of 90 grams